First and further-line multidisciplinary treatment of retroperitoneal sarcomas. Issue 4 (July 2022) - D'Ambrosio, Lorenzo; Van Houdt, Winan; Stelmes, Jean-Jacques; Gronchi, Alessandro
Abstract : Purpose of review: To review current knowledge and recent advances in retroperitoneal sarcoma management. Recent findings: Surgery, radiotherapy, and medical treatments of retroperitoneal sarcomas should take into account the peculiarities of each histotype and the unique anatomical site. Surgery remains the mainstay of treatment and the only chance of cure for these diseases. In low-grade retroperitoneal sarcomas, like well differentiated liposarcoma, where the leading cause of death is dominated by local rather than distant relapses, treatment of the primary tumor encompasses extended surgery with multiorgan resection and evaluation of preoperative radiotherapy. Conversely, surgery is usually more conservative and without radiotherapy in those retroperitoneal sarcomas, such as leiomyosarcoma, characterized by a high risk of metastatic spread that prompted also the evaluation of neoadjuvant, histotype-driven chemotherapy. Surgery might have a role also for relapsed disease, despite long-term disease control probability declines at each recurrence. In advanced stages, anthracyclines still retain a key role and all medical treatment strategies should follow the specific chemosensitivity of each histotype to improve patient's outcomes. Summary: The rarity and heterogeneity in biological behavior and clinical presentation of retroperitoneal sarcomas deserves a multidisciplinary and histotype-driven treatment at all stages of the disease to be performed in highly specialized centers.